2010
DOI: 10.1063/1.3449128
|View full text |Cite
|
Sign up to set email alerts
|

Metal-oxide-semiconductor tunneling photodiodes with enhanced deep depletion at edge by high-k material

Abstract: Metal-oxide-semiconductor (MOS) photodetector with the high-k material enhanced deep depletion at edge was demonstrated. The mechanism of saturated substrate injection current in MOS capacitor was adopted. By building HfO2 based devices that with the direct observation of the enhanced edge charge collection efficiency due to fringing field effect in inversion, we are able to show a photodetector with 3000 times (ratio of photocurrent to dark current) improvement in sensitivity than the conventional SiO2 based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The critical field analysis suggests that the edge field dominates the C-V curve behavior until the bulk start to go into deep depletion region. The field ratio between edge and bulk for HfO 2 /SiO 2 is 1.21 as shown in Fig 5. The result is consistent to the previous study that the deep depletion occurs earlier in HfO 2 /SiO 2 than in SiO 2 due to enhanced edge field by high-k material [3].…”
Section: Correlation Between C-v Curves and Edge Field Enhanced Deep supporting
confidence: 95%
See 3 more Smart Citations
“…The critical field analysis suggests that the edge field dominates the C-V curve behavior until the bulk start to go into deep depletion region. The field ratio between edge and bulk for HfO 2 /SiO 2 is 1.21 as shown in Fig 5. The result is consistent to the previous study that the deep depletion occurs earlier in HfO 2 /SiO 2 than in SiO 2 due to enhanced edge field by high-k material [3].…”
Section: Correlation Between C-v Curves and Edge Field Enhanced Deep supporting
confidence: 95%
“…The tunneling induced deep depletion expansion-shrinkage has been enhanced by the edge field of abrupt junction in the MOS structure during illumination [3] as shown in Fig.1 of the SiO 2 and HfO 2 devices. …”
Section: Correlation Between J-v Curves and Edge Field Enhanced Deep mentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, it is noticed that the inversion current of MOS photodiode with specific perimeter dependency was reported. 23,24 However, in this work, it was found that the I-V characteristic of sample 3H shows area but not perimeter dependency when measured under illumination with high intensity. Current conduction mechanism was also proposed for this observation.…”
Section: Introductionmentioning
confidence: 57%